The Relationship of Zakat Management Organization (ZMO) to the Effectiveness of Higher Education Management - Syahputra, Angga; Kaswinata, Kaswinata; Siregar, Saparuddin; Marliyah, Marliyah; Waeno, Muhamadaree (Idarah (Jurnal Pendidikan dan Kependidikan), 2023)
This research aims to analyze the transformation of zakat management as a construct for the development model of independence in higher education institutions in Indonesia. Identifying  zakat management includes differences in religious interpretations, regulatory ambiguity, and management ineffectiveness . The research adopts a qualitative descriptive survey method conducted at the Islamic University in Medan, North Sumatra. The study highlights the symbiotic relationship between zakat management organizations and educational institutions, emphasizing the important role of zakat in supporting financially disadvantaged students. Through collaboration, universities can actively identify  deserving recipients and promote social responsibility. Zakat institutions emerge as financial entities and development partners, empowering beneficiaries towards economic independence. The research findings also indicate the effectiveness of zakat distribution through several means, including providing scholarships, improving educational infrastructure, enhancing education quality, and promoting equal opportunities in higher education. This study advocates for integrating justice, transparency, and sustainability in zakat operations, positioning these institutions as pillars supporting economic and social development in Islamic society. This research identifies current challenges in the zakat management system and proposes solutions to enhance its effectiveness in Indonesia, a Muslim majority country.